Adjusting the Electrolyte Polarity to Address the Dissolution Issue of Organic Electrode. Issue 1 (24th November 2022) - Liu, Zitong; Xu, Ting; Meng, Xianjiao; Zhao, Yali; Lan, Qing; Liu, Yutao; Song, Zhiping; Qin, Jian; Zhan, Hui
Abstract: Small organic molecules with carbonyl active site are a prominent member in the family of organic electrode material, due to the reversible reaction and more tunable electrochemical property. However, the dissolution loss is the biggest obstacle in its application. In this work, we tried to address the dissolution issue of 5, 7, 12, 14‐pentacenetetrone (PT), a typical quinone‐based organic electrode. Highly concentrated electrolyte of 5 M LiTFSI DME was used and it significantly reduced the dissolution and well maintained the capacity after 500 cycles. Besides, through the investigation of the relationship between solvent/electrolyte property and dissolution, and the interaction between electrode and electrolyte, a guiding rule of the dependence of dissolution on polarity was proposed. With the rule, non‐polar solvent of hexane was further added as co‐solvent and its‐adding decreased the polarity and substantially eliminated the dissolution loss. The work supplies a common electrolyte strategy to address the dissolution issue of small organic molecules. Abstract : Highly concentrated electrolyte of 5 M LiTFSI DME much assists the stable cycling of 5, 7, 12, 14‐pentacenetetrone (PT), and polarity adjustment rule further address the dissolution issue of small organic molecules.